Insights on the neurocognitive mechanisms underlying hippocampus-dependent memory impairment in COVID-19 - Meyer, Patric; Zaiser, Ann-Kathrin (Scientific reports, 2025)
COVID-19 has been linked to acute and long-term cognitive impairments, including memory and concentration deficits, as well as neuropsychiatric symptoms such as anxiety and depression. However, the neuropathophysiological mechanisms underlying these cognitive and affective changes remain poorly understood. Accumulating evidence points towards neuroinflammation as a potential driver of most acute and post-acute neurofunctional symptoms. In this study, we aimed to comprehensively characterize cognitive impairment associated with COVID-19 using a large online cohort of over 1400 participants, including individuals reporting a previous SARS-CoV-2 infection and individuals who had never been tested positive. Our cognitive test battery covered alertness, executive functions, and episodic long-term memory. Our results demonstrate a pronounced and selective impairment of individuals previously infected in a mnemonic discrimination task known to engage hippocampus-dependent pattern separation. This impairment remained statistically significant after controlling for potential confounding factors (i.e., age, gender, education, depressiveness, anxiety, and stress). This finding, derived indirectly from behavioral performance, suggests compromised hippocampal neurogenesis following infection, which may contribute to COVID-related memory deficits. Our study has important implications for understanding the neurofunctional consequences of COVID-19 and highlights the potential significance of neuroinflammation in the manifestation of cognitive impairments.
Gesehen am 27.10.2025